Community Economic Empowerment through Waste Bank Initiatives: A Case Study of the Berseri Waste Bank in Bengkalis Regency, Indonesia - Tengku Wikel Novryan; Muhammad Firdaus; Yasir (Economics and Business Journal (ECBIS), 2026)
The global paradigm shift in waste governance towards a circular economy has driven the adoption of Community-Based Solid Waste Management (CBSWM), widely manifested in Indonesia through the Waste Bank initiative. Although theoretically designed as an ecological mitigation instrument and a catalyst for economic empowerment, previous literature remains dominated by techno-ecological and urban biases. These studies often overlook the structural dynamics of community empowerment in areas lacking established recycling infrastructure. This study aims to fill this gap by investigating the economic empowerment mechanisms and institutional resilience of the Berseri Waste Bank in Bengkalis Regency, a coastal-island area facing logistical disruption constraints. This study employed a qualitative approach with a case study design, involving 10 multi-actor informants (government, managers, customers, and community leaders) selected through purposive and snowball sampling. Data were collected via in-depth interviews, observations, and document reviews, with data credibility ensured through source and method triangulation. The results reveal four main findings: (1) increased environmental awareness that reduces open burning practices; (2) increased real household income; (3) the emergence of micro-scale circular logistics practices; and (4) community participation heavily driven by social capital (trust and local leadership). Theoretically, this study extends the application of circular economy theory by proving its viability at the micro-community level in geographically isolated regions. As a practical implication, this study recommends that local governments formally recognize waste banks as legitimate circular economy entities and provide policy interventions in the form of coastal transportation logistics subsidies